Effect of music in female college soccer players during a maximal treadmill test - Young, S. C.; Sands, C. D.; Jung, A. P. (International Journal of Fitness, 2009)
The effect of listening to music on highly trained athlete`s work output, rate of perceived exertion (RPE), and heart rate (HR) during a maximal treadmill test was examined. Fifteen female varsity college soccer players (age 20.4±1.0 yrs; ht-163.8±5.1 cm; wt=60.0±4.3 kg) ran to volitional exhaustion on two separate occasions. Participants ran one trial while listening to pre-selected music at 90 decibels and the second trial was run without listening to music. Dependent t-tests were used to determine that there were no significant differences found in the TTE or maximal HR between the music and no music trial (p<0.05). A repeated measures ANOVA showed no significant difference in HR or RPE between trials at any stage (p=0.53). Evidence from this study suggests that music will not affect running performance or perception of effort in trained individuals. Future research should evaluate how different types and intensities of music affect work output and RPE in trained individuals.